SYSTEMATIC ANALYSIS OF MEDICINAL PLANTS - Shukurova Shoxina Tuyg’unovna (Лучшие интеллектуальные исследования, 2024)
Abstract. In this article, the requirements for the study of medicinal plants and the systematic analysis of medicinal plants are covered. can be obtained.